Beyond traditional clinical measurements for screening fears and phobias - Rosa, P. J.; Esteves, F.; Arriaga, P. (IEEE Transactions on Instrumentation and Measurement, 2015)
The use of eye movements is a usual method of measuring attentional and emotional response in laboratory. However, when it comes to clinical practice, it is seldom applied. Two studies were conducted to examine whether extraocular and intraocular movements can be used as indices of attentional bias and autonomic activation. In the first study, a free-viewing task, combined with subliminal exposure, showed that high-fear individuals tend to orient more their attention toward the visual space where threat-stimuli (snakes) were presented. The findings suggest a reflexive overt attentional orienting bias for subliminal snakes in comparison with subliminal control stimuli. The differentiation between participants with high and low fear of snakes suggested that a disposition to fear snakes affects the initial ocular saccades. In the second study, participants were instructed to discriminate a sign that was randomly displayed at the center of the display while subliminal images were peripherally presented. The results revealed larger pupil dilation for threatening stimuli subliminally presented; again, high-fear individuals showed larger pupillary dilations, independently of the stimulus category. Our results are in line with the assumption that a predisposition to fear is relevant for extraocular and intraocular movements when exposed to threat stimuli. These findings suggest that eye measurements, combined with subliminal exposure techniques, could be a reliable and nonintrusive aid tool to be used for the assessment and treatment of fear and phobias.